Antimicrobial Activity and Chemical Composition of Coriander & Galangal Essential Oil - Özkınalı, Sevil; Şener, Nesrin; Gür, Mahmut; Güney, Kerim; Olgun, Çağrı (Manuscript Technomedia LLP, 2017)
Essential oils were obtained from Coriandrum sativum and Alpinia officinarum through steam distillation method in this study. Antimicrobial activities of the obtained essential oils were investigated by using minimum inhibitory concentration (MIC) test by against 18 different species microorganisms. It was found that the C. sativum had strong antimicrobial activities against the 14 tested microorganism and A. officinarum oils showed strong antimicrobial activity against the 7 tested microorganisms. Furthermore, the contents of the essential oils were determined with GC-MS analyses. The most abundant compounds of essential oils of A. officinarum and C. sativum were determined as 28.4% eucalyptol and 69.4% linalool. As a result, it can be easily said that the essential oils of C. sativum and A. officinarum can be used as antimicrobial protector in related fields. © 2017, Association of Pharmaceutical Teachers of India. All rights reserved.
Keywords: A. Officinarum; C. Sativum; GC-MS; Antimicrobial Activity; Essential Oil